Chad Public Expenditure Review in the Agricultural, Rural Development, and Food Security Sector - World Bank (Washington, DC, 2015)
Over the review period covered by this report (2003-2012), the budget allocated to agriculture increased noticeably more than the sector’s contribution to GDP. This reflects a notable effort by the Chad authorities to increase the budget to boost this sector’s development in recent years. In this proactive context, Chad signed its CAADP compact in December 2013 to continue supporting agriculture’s revival. The CAADP is being implemented in Chad even as the terms of the National Rural Sector Investment Program (PNISR, 2014-2020) are being finalized. Within the context of the CAADP, the Government of Chad (GOC) wished to undertake a review of public agriculture expenditures to learn from past budgetary implementation in this sector with a view to improving future program performance. Following a request by the Ministry of Agriculture and Irrigation (MoAI), the NEPAD planning and coordination agency gave Chad it’s backing for this review. This process was undertaken by the Program for Strengthening National Comprehensive Agricultural Public Expenditure in Sub-Saharan Africa, co-financed by the Bill and Melinda Gates Foundation and the CAADP Multi-Donor Trust Fund. This program, implemented by the World Bank, aims to improve the impact of the still-limited public resources available to governments in Sub-Saharan Africa to foster agricultural development and reduce poverty in rural areas, where most of the poor in these countries, notably Chad, live. This study follows and builds upon a number of similar studies conducted in recent years on public expenditure management, in particular in Chad the Action Plan for the Modernization of Public Finances (PAMFIP). However, these studies have focused on budget management as a whole, and none to date has looked at the agricultural sector specifically.